1997
DOI: 10.1002/(sici)1096-8644(199712)104:4<513::aid-ajpa6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and survival of elements and element portions in the bones of the Crow Creek massacre victims

Abstract: The interpretation of archaeologically-derived skeletal series is dependent on the elements and portions of elements preserved for examination. Bone and bone portion survival is affected by factors, both intrinsic and extrinsic to the elements themselves, that influence deterioration and preservation. Among the intrinsic variables, the density of the element and element portion are particularly important with respect to the degree of preservation. Recently reported bone mineral density values from a contempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 16 publications
4
42
0
2
Order By: Relevance
“…related to anatomical structure, size, and bone density) and extrinsic (i.e. taphonomic, natural or cultural) factors influencing preservation in human bone deposits (e.g., Willey et al, 1997;Knüsel and Outram, 2004;. Despite these advances, 'preservation' in most bioarchaeological studies remains imprecise, used to imply interchangeably bone quantity, fragmentation, surface condition, and/or skeletal part representation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…related to anatomical structure, size, and bone density) and extrinsic (i.e. taphonomic, natural or cultural) factors influencing preservation in human bone deposits (e.g., Willey et al, 1997;Knüsel and Outram, 2004;. Despite these advances, 'preservation' in most bioarchaeological studies remains imprecise, used to imply interchangeably bone quantity, fragmentation, surface condition, and/or skeletal part representation.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison was used to finally determine the taphonomic character of each assemblage, distinguishing between natural and cultural formation processes. The intrinsic patterns have been established by studies on bone mineral density (e.g., Willey et al, 1997) and BRI analysis of documented collections of complete skeletons affected by minimal or no cultural disturbance . When the observed patterns differ considerably from intrinsic preservation patterns, a cultural cause of the disturbance can be inferred.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, many of the skeletal elements recovered from the mainland were hand and foot bones that generally do not have a high frequency of survivability Waldron 1987;Willey 1990;Willey et al 1997). Many of the wellpreserved foot and hand bones did not exhibit signs of weathering or decay consistent with tropical environments.…”
Section: Tumba Tres (Burial Three)mentioning
confidence: 99%
“…The results suggested that the mid-shaft regions of the long bones have substantially higher bone density than the proximal and distal regions; this appears to support the theory that the mid-shafts of long bones tend to be preserved in large numbers. Other studies include Willey et al (1997), who examined bone mineral density in two skeletal collections, namely, the Crow Creek Massacre site and a contemporary sample using single photon absorptiometry. They found that certain limb bones have segments of higher density such as which may show greater representation in the archaeological record.…”
Section: Bone Mineral Density Studies In Archaeological Human Remainsmentioning
confidence: 99%
“…According to this model, bone mass achieved by early adulthood is a key determinant of As a result many methods of measurement and reference samples are widely available within the clinical literature (Table 1). With regard to the measurement of BMD in past populations, several studies have been conducted on adult skeletons (Elenman et al 1995;Holck 2007;Lynnerup and Von Wowern 1997;Mays 2001;Mays et al 2006) and some juvenile samples (McEwan et al 2005;Willey et al 1997;Bennike et al 2005;Manifold 2008;Kendell and Willey 2013). This paper aims to review the literature on bone density in children from clinical and anthropological contexts.…”
Section: Introductionmentioning
confidence: 99%